1970
DOI: 10.2466/pms.1970.31.3.919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of One Day of Sensory Deprivation on a Battery of Open-Ended Cognitive Tests

Abstract: In an attempt to test the hypothesis that performance on unstructured or open-ended cognitive tests will be impaired by sensory deprivation (SD), the Guilford battery of creative thinking, consisting of 10 subtests, was administered to a group of 18 experimental Ss before and after one day of SD. The results showed that, relative to a group of 18 controls, only the performance on associational fluency was significantly impaired. Three possible explanations were offered for these essentially negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In addition to its use in evaluating the patient’s state and diagnosis, sensory stimulation has been also proposed as an intervention strategy to enhance the patient’s engagement with the immediate environment and to increase her/his consciousness level ( Canedo et al, 2002 ). The background tenets for supporting stimulation initiatives include (a) the general fear that sensory deprivation connected with the virtual isolation of the person after severe brain injury may have additional negative effects on her/his condition ( Oleson and Zubek, 1970 ) and (b) the view that the plasticity of the central nervous system could definitely benefit from a rich stimulation regimen ( Canedo et al, 2002 ; Lombardi et al, 2002 ; Elliott and Walker, 2005 ). The use of sensory stimulation for DOC patients has gained popularity during the 1980s, but beliefs and opinions about its effectiveness vary substantially among health professionals.…”
Section: Using Stimulation To Evaluate and Restore Cognitive Functionmentioning
confidence: 99%
“…In addition to its use in evaluating the patient’s state and diagnosis, sensory stimulation has been also proposed as an intervention strategy to enhance the patient’s engagement with the immediate environment and to increase her/his consciousness level ( Canedo et al, 2002 ). The background tenets for supporting stimulation initiatives include (a) the general fear that sensory deprivation connected with the virtual isolation of the person after severe brain injury may have additional negative effects on her/his condition ( Oleson and Zubek, 1970 ) and (b) the view that the plasticity of the central nervous system could definitely benefit from a rich stimulation regimen ( Canedo et al, 2002 ; Lombardi et al, 2002 ; Elliott and Walker, 2005 ). The use of sensory stimulation for DOC patients has gained popularity during the 1980s, but beliefs and opinions about its effectiveness vary substantially among health professionals.…”
Section: Using Stimulation To Evaluate and Restore Cognitive Functionmentioning
confidence: 99%
“…It is suggested that the length of the test battery, a neglected variable in sensory deprivation research, may be a crucial factor; the administration of tests, by disrupting the deprivation situation, diminishes the very effect it is designed to measure. Oleson and Zubek (1970) found that one day of sensory deprivation decreased associational fluency but did not affect performance on nine other tests of creative thinking (Guilford, 1964). The authors mention three explanations for this non-replication of the more usual finding that there are decrements on unstructured cognitive tasks after sensory deprivation (reviewed in Suedfeld, 1969a).…”
mentioning
confidence: 97%
“…
Oleson and Zubek ( 1970) found that sensory deprivation for 24 hr. did not produce significant deterioration in creative thinking and offered several possible explanations for this datum.
…”
mentioning
confidence: 97%
“…According to the literature using this test certain kinds of memory deficits, i.e. those connected with sensory deprivation (Oleson and Zubek 1970) and senile dementia (Weingartner et al 1981) but also sex-related differences (Olive 1972) can be detected.…”
Section: Intensity Of Attention (Symbol Cancellation Test)mentioning
confidence: 99%